Is the Individual Subordinate to the City? A Response through a Consideration of Contemplation - Gutschke, Daniel (The Thomist, 2025)
The relationship between the individual person and the political community has been intensely debated by disciples of St. Thomas Aquinas. On the one hand, St. Thomas teaches that the whole is more perfect than the part, which suggests that the individual is ordered to the city as to an end. On the other hand, he holds that man's happiness consists principally in contemplation, which might seem to imply that the city is ordered to the private happiness of the individual. In order to understand St. Thomas's account of the relationship between the individual and the city, one must recognize contemplation itself as a common good that is the chief goal of the city and that is engaged in by the city as such. For St. Thomas, the common good of the political community is the shared life of virtue. This shared life of virtue is realized most fully when citizens delight in the truth together. This shared contemplation finds its supernatural perfection in the act of Christian worship. This understanding of the relationship between contemplation and the common good reveals that it is precisely in the act of contemplation that one most fully fosters and participates in the common good of the city.